Dynamic Community And Modern Islamic Applications: The Study Of Muhammad Abduh's Epistemology - Nurisman NURISMAN; Iqbal Haraka MAHENDRA (International Journal of Environmental, Sustainability, and Social Science, 2022)
Since entering the era of decline, Muslims no longer produce outstanding achievements in the field of science. Western scholars then developed science with the materials developed from the work of Muslim scholars. Of course, there are weaknesses inherent in Western civilization. However, they creatively produce new things to be studied. In the 19th century, scientific optimism was partly due to the emergence of the theory of Darwin (Charles Darwin), Herbert Spencer (Social Darwinism), before Agust Comte, and so on. Abduh himself met Herbert Spencer in England. The findings of Western intellectuals became the subject of discussion by Muhammad Abduh. Islam is not against science. This is what Muhammad Abduh often said. The Islamic thought reform movement is a challenging study and continues to be explored. One fundamental challenge faced by Muslim thinkers in the 19th century was the decline of Islam. This demands to be solved and found a solution. How did Islamic reformers respond to the challenges of the tough times? Good because, factually, Muslims are in a lagging position. Also, many Muslim countries are under the occupation of the West.